E0316 The sCD40L and circulation endothelial progenitor cells change of danhong combined naoxintong therapy to acute coronary syndrome patients with percautious coronary intervention. (17th November 2010) - Jing-qian, Lu; Yi, Li; Yun, Lv; Ya-ping, Pan; Yan, Gao; Feng, Yang
Abstract : Objective: To observe the effects of Danhong injection combined naoxintong pills with acute coronary syndrome (ACS) patients who accepted percautious coronary intervention (PCI) about recelently outcome and changes of blood serum soluble CD40 ligand (sCD40L) and Circulation Endothelial Progenitor Cells (EPCs). Methods: 91 ACS patients with PCI therapy were randomly divided into Buchang group (n=48) and normaltherapy group (n=43), after PCI, normaltherapy group were given coronary heart disease second prevention drugs, and Buchang group were added danghong and naoxintong at the basis of coronary heart disease second prevention drugs. the outcome after PCI 3 months, 6 months and changes of sCD40L and EPCs were observed. Results: In two groups, cardiac death, myocardial infarction, stroke, angina, re-hospitality were no significantly difference (p>0.05) but the left ventricular ejection fraction were more higher in Buchang group than normaltherapy group (61.5% vs 55.3%, p<0.05). 6 miniters walk distence test were more higher in Buchang group than normaltherapy group (562 m vs 513 m, p<0.05) at 3 months after operate. Still after 6 months, the left ventricular ejection fraction were more higher in Buchang group than normaltherapy group (65.3% vs 60.8%, p<0.05). 6 miniters walk distence test were more higher in Buchang group than normaltherapy group (541 m vs 502 m, p<0.05). Moreover after 3 months, the level of sCD40L were lower in Buchang group than normaltherapy group (2.23 ng/ml vs 2.62 ng/ml, p<0.01), the numbers of EPCs were more in Buchang group than normaltherapy group (37.1±5.8 vs 32.4±4.6, p<0.05). Conclusion: These study suggested that Danhong injection combined naoxintong pills could decreased sCD40L level, increased EPCs level, improved cardia function at ACS patients with PCI therapy, It was worthy for deeply research.